Effect of Welding Current on Mechanical Properties of Aluminum Alloys in Dissimilar Joint by GTAW Process - Riswanda, Riswanda; Sugianto, Sugianto (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Welding technique is one of the process connection metal in the manufacturing industry. Aluminum alloys have several advantages including: light, good electrical and corrosion resistant properties. Welding application of dissimilar aluminum alloys with the 5083 and 6061-T6 series such as building structures, bridges, railroad frames, ships and oil platforms. The joining of dissimilar aluminum alloys by welding technique is difficult because the metal has different thermophysis properties. The study aimed of this research to analyze the mechanical properties of variation welding current on joint area GTAW. Visual observation shows that the joint specimen with the low current (100 A) has low penetration in welding groove, whereas at the high current (140 A) undercut occurs on the side of the weld seam, there are spatter and deposits (excessive added material). The hardness test with the current 120 A shows the regular distribution and has the highest tensile test of 201 MPa.